Effect of maltodextrin addition on the preparation of lipase from Coconut haustorium. Issue 1 (April 2021) - Suloi, ANF; Mahendradatta, M; Laga, A; Suloi, AF
Abstract: Lipase is a biocatalyst that hydrolyzes esters bonds such as triglycerides to produce free fatty acids and glycerol. Coconut haustorium is an unused source of lipase enzyme. One of the methods in the preparation of the lipase enzyme from coconut haustorium that ready to be used is by a drying process. However, the drying process can damage the structure of the enzyme and decreases its activity. Therefore, the maltodextrin is required to protect the structure of the enzyme during the drying process. This study aims to identify the effect of maltodextrin addition to the lipase enzyme preparation. This study started by shredding coconut haustorium to reduce the size. Then, the maltodextrin at concentrations 0%, 10%, and 20% was added to the coconut haustorium. The mix was then dried using a blower oven with a temperature of 40°C for 9 hours. The parameters tested in the study were protein content, enzyme activity, water content, and yield. The best treatment in the preparation of the enzyme lipase from coconut haustorium was the addition of 20% maltodextrin. This treatment gave the highest activity of 0.438 U/ml, protein content of 7.618 mg/ml, the specific activity of 0.058 u/mg protein, the water content of 18.96% and yield of 26.71%.